2013
DOI: 10.3892/mco.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

Tumor characteristics and metastatic sites may predict bevacizumab efficacy in the first-line treatment of metastatic colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) is among the most frequently diagnosed cancers and a major cause of cancer-related mortality worldwide. The aim of the present study was to determine whether there was an improvement in the time to disease progression (TTP) in patients with metastatic colorectal cancer (mCRC) treated with first-line bevacizumab plus chemotherapy, according to tumor characteristics and metastatic sites. Tumor characteristics and tumor burden were considered to be predictive markers of the thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This is reinforced by the fact that these parameters are related to wash-in only. Varol et al [29] reported that tumor characteristics might predict bevacizumab efficacy in the first-line treatment of metastatic colorectal cancer, as assessed with CEUS baseline values. O'Connor et al [24] identified microvascular heterogeneity assessed by MRI techniques and image processing as important prognostic and/or predictive biomarkers in 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is reinforced by the fact that these parameters are related to wash-in only. Varol et al [29] reported that tumor characteristics might predict bevacizumab efficacy in the first-line treatment of metastatic colorectal cancer, as assessed with CEUS baseline values. O'Connor et al [24] identified microvascular heterogeneity assessed by MRI techniques and image processing as important prognostic and/or predictive biomarkers in 10 patients.…”
Section: Discussionmentioning
confidence: 99%